The The Cutting-Edge of English Learning: Augmented Reality in Classroom Insights - Izzah, Nurul; Latifa, Ammang; Nur, Rafi'ah (ETERNAL (English, Teaching, Learning and Research Journal), 2025)
This study aims to recount the perceptions and experiences of students on integrating Augmented Reality (AR) in Learning English for Junior High School. This study is quantitative in nature by using 32 seventh grade students as treatment through AR-based learning tools. The dimensions are based on the 1-5 Likert scale-based questionnaire of ease of use, learning usefulness, technological features, and learning outcomes. Data was analyzed descriptively to describe the pattern of students' experiences and perceptions of AR technology. The results showed that AR had a positive impact on student motivation, engagement, and understanding. 77% of the students were found to be in the medium learning experience category, and 17% were found in the high category, showing that AR managed to produce significant learning experience. AR interactive functions allow students to learn better complex concepts visually and interactively; that said, AR applications in mastering complex information is still in the process of development. A limitation in the present study includes limited coverage of the population, with most studies having used quantitative approaches that did not give in-depth insight into students' experiences. Day, future studies should include a broader population as well as applying qualitative approach to get a holistic understanding. This study argues that AR is more than a technological development, it is a pedagogical strategy that can enhance the quality of English learning. The results can play a crucial role for educators, curriculum developers and policy decision makers for preparing learning strategies suitable for the needs of students in the digital age”. Keywords: Augmented reality, student experience, student perception, English language learning, technological innovation.